India's Water Economy : Bracing for a Turbulent Future - Briscoe, John; Malik, R.P.S. (New Delhi: Oxford University Press, 2012)
India faces a turbulent water future and the current water development and management system is not sustainable.Unless dramatic changes are made and made soon in the way in which government manages water, India will have neither the cash to maintain and build new infrastructure, nor the water required for the economy and for people. This Report examines the evolution of the management of India's waters, describes the achievements of the past, and the looming set of challenges. The Report suggests what changes should be considered and how to manage the transition from the ways of the past to the ways of the future in a principled but pragmatic manner. This report focuses on two basic issues-the major water-related challenges facing India, and the critical measures required to address them. It calls for a reinvigorated set of public water institutions to sustain water development and management in India. The study examines the evolution of water management in India, describes the achievements of the past, analyses the challenges ahead, and suggests ways of evolving a sustainable water management system.